On Some Sets in Digital Topology (International Journal of Food and Nutritional Sciences, 2022)
The notations of strong and week forms of open sets and closed sets in the digital line anddigital plane have been used in digital image filtering techniques. The purpose of this paper is tocharacterize t\such sets in Digital Topology with special reference to α – closed and α- open sets.